Unstacking high temporal resolution meteorological data for multidimensional analysis of climate variability in southern Burkina Faso. Issue 2 (2nd July 2016) - Borona, Mwenda; Mbow, Cheikh; Ouedraogo, Issa
Abstract: Climate variability, expressed by random short time variation in rainfall and temperature, has severe effects on agriculture in the Sahel. This region depends on a short and uncertain rainy season with many uncertainties in short-term climate variations that affect farm decisions in regards to. sowing period, crop variety, water management, etc. The most conspicuous climate variability issue in West Africa is the high intra-seasonal and inter-annual variability associated with dry (or too wet) spells, and in most cases, season length modifications. We derived selected climate descriptors from 35-year daily climate data to assess inter-annual rainfall anomalies, seasonal variation and temperature trends in southern Burkina Faso. Results show the evolution in the number of rainy days and rainfall sum from the drier years in the late 1970s and early 1980s, which were followed by positive but variable rainfall in the 1990s and 2000s. We further observed widespread occurrence of unsuccessful season onsets in more than 50% of the study period. Short dry spells of 5–10 days dominate most of the years with longer spells at onset shortening the season. The results could be used to orientate interventions aimed at providing well-packaged forecasts for adaptation needs.